Association of risk factors, clinical presentation, and treatment with neonatal outcomes among pre-eclamptic and eclamptic women: a cross-sectional study - Bukhari, Syeada Nawal; Jamil, QurratulAin; Ihsan, Beenish; Jamil, Muhammad Nauman; Bukhsh, Allah; Hayat, Khezar; Rehman, Anees ur; Khan, Jawad Akbar; Iqbal, Shahid Muhammad (Frontiers in Global Women's Health, 2025)
BackgroundEclampsia and pre-eclampsia cause high feto-maternal mortality in Pakistan. This study aimed to identify potential risk factors in pregnant women that can lead to the development of eclampsia and pre-eclampsia.MethodsA cross-sectional study was conducted in the BVH, Bahawalpur (July 2021–December 2022), to record socio-demographic information, risk factors, clinical symptoms, and treatment administered, which was linked with maternal and neonatal outcomes. The Chi-squared test was applied to describe the relation in categorical variables. Odds ratio were calculated by binary logistic regression for normally distributed significant values.ResultsA total of 85 women with eclampsia and 43 with pre-eclampsia were included in the study. The eclamptic women showed a higher rate of illiteracy, were overweight, and married to their cousins. They presented with high systolic blood pressure, proteinuria, and low platelet count (OR = 7.24, 95% CI = 1.60–32.68, p = 0.01), increased respiratory rate, and elevated AST, ALT, and LDH levels at the time of diagnosis. Women administered with MgSO4 10 g/day (48.5% survived vs. 77.4% non-survived) showed high perinatal mortality compared to a 4 g/day dose (30.9% survived vs. 16.1% non-survived) or those who hadn't received magnesium sulfate (20.6% survived vs. 6.5% non-survived).ConclusionAdvanced maternal age (≥35), overweight, elevated AST, ALT, and LDH levels, consanguinity, and grand multiparity were associated with higher perinatal mortality. Women with these predictive factors should be monitored for the development of pre-eclampsia or eclampsia.